Starch Nanocomposite Films: Migration Studies of Nanoparticles to Food Simulants and Bio-Disintegration in Soil - Ortega, Florencia (2022)
In this work, films containing AgNPs were obtained by different green synthesis techniques (AgNP in situ and AgNP L). The inclusion of nanoparticles in the starch matrix improved both mechanical and barrier properties. The migration of AgNPs from the nanocomposite material to three food simulants (water, 3% v/v acetic acid and 15% v/v ethanol) was studied. The experimental data were fitted by using different widely accepted mathematical models (Fickian, Ritger and Peppas, and Weibull), indicating that the AgNP migration followed a complex mechanism. The silver concentration (mg Ag per kg of simulant) that was released from the nanocomposite films was higher for the samples with AgNPs in situ than for those containing AgNP L. Likewise, the maximum release value (0.141 mg/dm2 for AgNPs in situ in acetic acid simulant) was lower than the limits proposed by the legislation (European Commission and MERCOSUR; 10 and 8 mg/dm2, respectively). The replacement of conventional plastic materials by biodegradable ones requires the evaluation of biodisintegration tests in soil. In this sense, a period of 90 days was necessary to obtain ≥50% weight loss in both nanocomposite films. Additionally, the bio-disintegration of the samples did not contribute with phytotoxic compounds to the soil, allowing the germination of fast-growing seeds.